Konstitusi Islam Arab Saudi di Tengah Modernisasi - Cahyaning Putri, Ardhia Mutiara (UIN Alauddin Makassar, 2025)
For Saudi Arabia, modernization is one of the keys to releasing this country's dependence on oil, which has become its main commodity. MBS as the originator of Saudi Vision 2030 has carried out reforms to maximize other sectors in Saudi Arabia, such as politics, culture, education, society, law, and religion. However, the reforms carried out by MBS contain many freedoms which raise pros and cons for the Muslim community of Saudi Arabia and the world. This paper seeks to explore how moderate Islam initiated by MbS easily accepts western modernization, namely with the Riyadh Season 2022 and the Halloween celebration which was first permitted by MbS, then the author will relate it to the Saudi Arabian constitutional system so far, not only that the author also will incorporate elements of Islamic law regarding the modernization phenomena that occurred after MBS served as Crown Prince and Prime Minister of Saudi Arabia. Finally, the author will include how the author views the presence of this modernization.